A STUDY ON SUBJECTIVE WELL-BEING AMONG BLUE COLLAR (IMMIGRANT) EMPLOYEEES AT SRI LAKSHMI SARASWATHI TEXTILES PUBLIC LIMITED – ARNI - Dr.N.Deepa, Mr.R.Rajesh, Mrs.P.Mohana Lakshmi, Mrs.V.Lakshmipratha (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
WELL-BEING is the condition of being happy, healthy, etc.., and it’s judging life positively and feeling good. Subjective well-being refers to how persons experience and appraise their lives, as well as their emotional experiences, overall life satisfaction, and sense of purpose or fulfilment. It encompasses both emotional reactions to daily experiences (hedonic well-being) and broader evaluations of life in general (evaluative well-being). Subjective well-being is about how the employees experience and evaluated their lives. Well-being in the work place is important for employee satisfaction, employee retention, Increase in employee productivity, etc., The wellbeing of employees is a good in itself. But an important question frequently arises as to whether there are any objective benefits to making the subjective wellbeing of workers a priority. Clearly, implementing policies that promote worker wellbeing can be resource- intensive. Subjective well-being is influenced by a variety of factors, including individual traits (like personality and temperament), life circumstances (such as income, health, and relationships), and societal factors (like cultural norms and social support). Research indicates that subjective well-being can fluctuate over time and is influenced by both external events and internal perceptions. This study reveals the immigrant employee perception (particularly textile workers) related to wellbeing like physical, career, economic, emotional, psychological etc.. Textile workers frequently work long hours, often exceeding time limits, and are frequently required to work overtime to meet production deadlines. This can lead to fatigue, stress, and a poor work-life balance. Textile manufacturing involves operating heavy machinery and working with potentially hazardous materials. Lack of proper safety protocols, training, and protective equipment can lead to accidents and injuries.., A well structured questionnaire is used to collect the primary data. Sample size is 100.The researcher adopted simple random sampling for the study. The data was analyzed using statistical tools like Anova, Chi-square and Correlation